2022
DOI: 10.1038/s41467-021-27637-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic recovery of impulse propagation in myocardial infarction via silicon carbide semiconductive nanowires

Abstract: Myocardial infarction causes 7.3 million deaths worldwide, mostly for fibrillation that electrically originates from the damaged areas of the left ventricle. Conventional cardiac bypass graft and percutaneous coronary interventions allow reperfusion of the downstream tissue but do not counteract the bioelectrical alteration originated from the infarct area. Genetic, cellular, and tissue engineering therapies are promising avenues but require days/months for permitting proper functional tissue regeneration. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Such interventions would be promising to improve the depressed impulse propagation and reduce the spatiotemporally inhomogeneous electrical conduction on the infarct border zone and could attenuate genesis of re-entrant arrhythmias. In conjunction with this in vivo study, Lagonegro et al demonstrated a unique therapeutic intervention against arrhythmogenesis; local in-situ injection of multiple nanowires into the cryoinjured zone improved the depressed impulse conduction of the mouse heart (Lagonegro et al, 2022). Further studies are required to determine the feasibility of these promising strategies.…”
Section: Improvement Of Impaired Impulse Propagation By Mf Cx43 Knock...mentioning
confidence: 85%
“…Such interventions would be promising to improve the depressed impulse propagation and reduce the spatiotemporally inhomogeneous electrical conduction on the infarct border zone and could attenuate genesis of re-entrant arrhythmias. In conjunction with this in vivo study, Lagonegro et al demonstrated a unique therapeutic intervention against arrhythmogenesis; local in-situ injection of multiple nanowires into the cryoinjured zone improved the depressed impulse conduction of the mouse heart (Lagonegro et al, 2022). Further studies are required to determine the feasibility of these promising strategies.…”
Section: Improvement Of Impaired Impulse Propagation By Mf Cx43 Knock...mentioning
confidence: 85%
“…(3) Environmentally Friendly Applications . Exploration of new applications of SiC in clean energy, biomedicine, and environmental purification. While improving product quality, optimize the production process to reduce environmental pollution. …”
Section: Research Challenges and Perspectivesmentioning
confidence: 99%
“…Polymers (polyaniline and polypyrrole) and materials (MXene, graphene oxide, carbon nanotubes, gold nanorods/wires, poly(3,4-ethylenedioxythiophene):polystyrene sulfonate, silicon carbide nanowires, polyvinylidene fluoride, etc. ) were selected for their semiconductor or piezoelectric behavior to improve electrophysiological differentiation and synchronize the beating of cultured CMs and their precursors ( Dvir et al, 2011 ; Zhang et al, 2017a ; Tomecka et al, 2017 ; Ye et al, 2020 ; Alegret et al, 2022 ; Lagonegro et al, 2022 ; Mancino et al, 2022 ; Zhao et al, 2022 ; Ul Haq et al, 2023 ; Wu et al, 2023 ; Yin and Jiang, 2023 ). Of interest, various of these materials have been combined with bioinspired adhesive proteins derived from mussels, as dopamine used a crosslinker to reach improved superelastic and mechanical features of scaffolds based on polypyrrole or MXene ( Wang et al, 2016 ; Ye et al, 2020 ).…”
Section: Biomimetic Design: From Extracellular Matrix To Scaffoldmentioning
confidence: 99%